2014
DOI: 10.1177/0269094214521980
|View full text |Cite
|
Sign up to set email alerts
|

Governance and policy challenges of implementing urban low-carbon transport initiatives

Abstract: Emissions from transport represent a quarter of Scotland’s total. Action to significantly reduce greenhouse gas emissions from transport has been criticized for being limited, poorly integrated with other areas of policy and focused on narrow programmes. Several funding bodies at the European level provide funding for the development of pilot initiatives to reduce carbon and to promote knowledge exchange between partner cities. Cities where strategies have been successful consider transport as being a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…The main barrier identified is related to renewable energy technologies Giesekam et al (2014) Barriers were identified in the use of materials that contain less carbon throughout supply chains for the construction industry in the United Kingdom Garbuzova and Madlener (2012) The paper investigated the Joint Implementation and Green Investment Scheme as a possible means of attracting foreign investment in transnational projects, providing capital for the Russian energy sector with the goal of modernising operations, increasing energy efficiency and reducing carbon emissions Tait, Laing, and Gray (2014) Barriers to the implementation of low-carbon transport initiatives were studied in Aberdeen City Council, Scotland Lah (2015) The author highlighted the leading theoretical barriers to energy efficiency in the transport sector in a number of countries around the world and suggested policies to overcome them…”
Section: Articlementioning
confidence: 99%
“…The main barrier identified is related to renewable energy technologies Giesekam et al (2014) Barriers were identified in the use of materials that contain less carbon throughout supply chains for the construction industry in the United Kingdom Garbuzova and Madlener (2012) The paper investigated the Joint Implementation and Green Investment Scheme as a possible means of attracting foreign investment in transnational projects, providing capital for the Russian energy sector with the goal of modernising operations, increasing energy efficiency and reducing carbon emissions Tait, Laing, and Gray (2014) Barriers to the implementation of low-carbon transport initiatives were studied in Aberdeen City Council, Scotland Lah (2015) The author highlighted the leading theoretical barriers to energy efficiency in the transport sector in a number of countries around the world and suggested policies to overcome them…”
Section: Articlementioning
confidence: 99%
“…Literature shows that this problem is not confined to air travel behaviours. Habits pertaining to other travel modes are also hard to change (Nilsson & Küller, 2000;Tait, Laing, & Gray, 2014) raising questions about the habitual nature of travel decisions and the social identity associated with specific modes of transport. However, ideas around raising hypocrisy are worth pursuing because they may provide the key to lasting and meaningful change (Aronson, 1992;Dickerson et al, 1992;Fointiat, 2004;Hing et al, 2002) in a way that information providing alone has not done (Hopper & Nielsen, 1991).…”
Section: Implications For Changing Consumption Practicesmentioning
confidence: 99%
“…Recent work by the research team explored the manner in which sustainable transport best practice across the North Sea Region could be regarded as being transferable from one city to the next (Tait et al, 2014). By extension, a similar question could be asked with regards to similar institutions, or of organisations contemplating similar travel planning initiatives.…”
Section: Local Policymentioning
confidence: 99%